Re-Structuring Tanzania’s Investment Climate for Industrialization: Reflections from Industrialization Strategies in Malaysia - Ngowi, Honest Prosper (Journal of Policy and Leadership, 2019)
The paper engages to analyse the industrialization process in Malaysia and possible lessons that Tanzania can learn in its new industrialization move. The focus is on the industrialization strategies adopted by Malaysia from 1957 and Tanzania’s new industrialization move by the fifth phase government that came to office in 2015. Specifically the paper attempts to draw lessons related to investment climate in Tanzania from Malaysia’s industrialization strategies. Various industrialization strategies adopted by Malaysia over years are outlined followed by Tanzania’s new industrialization move. Then implications of Malaysia’s strategies for Tanzania’s new industrialization move are discussed in the context of investment climate for industrialization in general and Import Substitution Industrialization (ISI) and Export Oriented Industrialization (EOI) in particular. Several policy options for Tanzania to attain successful ISI and EOI are outlined as well.